The Level Of Farmers' Knowledge Of Modern Irrigation Technologies (Drip Irrigation And Sprinkler) A Field Study In Lattakia Governorate - Haddad, Khaldon Ahmad (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The research aimed to determine the level of knowledge of farmers in Lattakia governorate with modern irrigation technologies (drip irrigation and sprinkling), and study the difference between farmers in the level of knowledge of these technologies according to the variables of years of experience in agriculture and the scientific qualification of farmers. The researcher relied on the descriptive analytical approach, and the research community included all farmers in Lattakia governorate, and due to the researcher's inability to obtain an accurate number for the number of farmers, (200) questionnaires were distributed randomly, and (183) questionnaires valid for statistical analysis were retrieved. The results showed that the level of farmers knowledge in Lattakia governorate with modern irrigation technologies is a high level, with a relative importance (76.04%) for drip irrigation technology, and a relative importance (71.86%) for sprinkler irrigation technology, and the results also showed that the level of farmers' knowledge of these technologies increases with the rise of years of experience in Agriculture and the higher the qualification of the farmer. هدف البحث إلى تحديد مستوى معرفة المزارعين في محافظة اللاذقية بتقانات الري الحديث (الري بالتنقيط والرش), ودراسة الاختلاف بين المزارعين في مستوى المعرفة بهذه التقانات تبعاً لمتغيري سنوات الخبرة في الزراعة والمؤهل العلمي للمزارع. اعتمد الباحث على المنهج الوصفي التحليلي, وشمل مجتمع البحث جميع المزارعين في محافظة اللاذقية, ونظراً لعدم تمكن الباحث من الحصول على رقم دقيق لعدد المزارعين تمّ توزيع (200) استبانة بطريقة عشوائية, وتمّ استرجاع (183) استبانة صالحة للتحليل الإحصائي. أظهرت النتائج أنّ مستوى معرفة المزارعين في محافظة اللاذقية بتقانات الري الحديثة هو مستوى مرتفع, وبأهمية نسبية (76.04%) لتقنية الري بالتنقيط, وبأهمية نسبية (71.86%) لتقنية الري بالرش, كما أظهرت النتائج أنّ مستوى معرفة المزارعين بهذه التقانات يزداد بارتفاع سنوات الخبرة في الزراعة وبارتفاع المؤهل العلمي للمزارع.